Lecturers' Competence Levels and Goal Achievement of Universities in Kwara State - Olaifa, Adeseko Sunday; Hassan, Solawat Ajibola; Ayoku, Oba Baba; Shittu, Adesina Afeez; Haruna, Lauratu Sani (International Journal of Universal Education, 2025)
Background: Universities rely heavily on the competence of their lecturers to achieve excellence in teaching, research, and community service. In the context of growing digital transformation, institutions face the challenge of ensuring that lecturers possess adequate technological, pedagogical, and professional competencies to drive institutional effectiveness and maintain academic quality. Aim: This study aimed to investigate the relationship between lecturers’ competence levels and the achievement of university goals in Kwara State, Nigeria. Specifically, it sought to determine the levels of lecturers’ competencies, assess the extent to which universities achieve their institutional goals, and examine how each competence dimension contributes to overall goal attainment. Method: A descriptive correlational survey design was adopted for the study. The sample consisted of 333 lecturers selected from three universities using proportionate stratified random sampling. Data were collected through a validated instrument titled Lecturers’ Competence Levels and Goal Achievement Questionnaire (LCLGAQ). The data were analysed using mean and standard deviation to describe competence levels and goal achievement, while Pearson’s Product-Moment Correlation was used to test relationships among variables at a 0.05 significance level. Results and Discussion: Findings revealed that lecturers exhibited high levels of technological and professional competence, but moderate levels of pedagogical competence. University goals related to teaching and research were highly achieved, whereas community service goals showed moderate achievement. Statistical analysis indicated significant positive relationships between all competence dimensions and university goal achievement, with technological competence emerging as the strongest predictor. These findings underscore the critical role of lecturers’ competencies in enhancing institutional performance and achieving academic excellence. Conclusion: The study concludes that technological, pedagogical, and professional competences collectively determine the effectiveness of universities in accomplishing their teaching, research, and community service mandates. Strengthening lecturers’ competencies across these dimensions will enhance institutional capacity to meet core educational objectives and sustain competitive performance in higher education.